Hubungan Pola Asuh Orang Tua dengan Tingkat Stres pada Remaja - Nurliza, Ardillah; Sari, Niken Yuniar; Karim, Darwin; Sari, Tesha Hestyana (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Adolescence is a period in a person's life where they develop psychologically to find their identity. Teenagers who are vulnerable to experiencing various mental changes such as stress problems need guidance that includes certain parenting styles. A cross-sectional correlational descriptive design was used in this study. The research was conducted at SMAN 8 Pekanbaru with a population of 1,017 students at SMAN 8 Pekanbaru. The sample for this research was 287 respondents using purposive sampling technique. The Parental Authority Questionnaire (PAQ) questionnaire for parenting styles and the Depression Anxiety and Stress Scales Questionnaire (DASS 21) to assess stress levels in adolescents. This research uses univariate analysis, and bivariate analysis uses the chi square test. The results showed that the majority of respondents were female, 173 people (60.3%), the majority of respondents were 16 years old, 136 people (47.4%), and the majority of respondents were first-born children, 115 people (40.1%) . The majority of respondents in the study had a democratic parenting style and experienced normal levels of stress, 111 people (66.1%). Statistical tests show that there is a substantial relationship between parenting methods and stress levels in adolescents with p value (0.000) < alpha (0.05). Thus, it may be said that parenting styles have a significant relationship with stress levels in adolescents. Based on the findings of this study, more prevention and treatment options can be determined by implementing interventions to reduce stress in adolescents, especially due to parenting styles.